Monte Carlo simulations and experimental results on neutron production in the uranium spallation target QUINTA irradiated with 660 MeV protons. (July 2018) - Khushvaktov, J.H.; Adam, J.; Baldin, A.A.; Furman, W.I.; Gustov, S.A.; Kish, Yu.V.; Solnyshkin, A.A.; Stegailov, V.I.; Svoboda, J.; Tichy, P.; Tsoupko-Sitnikov, V.M.; Tyutyunnikov, S.I.; et al.
Abstract: The activation experiment was performed using the accelerated beam of Phasotron accelerator at the Joint Institute for Nuclear Research (JINR). The natural uranium spallation target QUINTA was irradiated with protons with energy 660 MeV. Monte Carlo simulations of neutron production were performed using the Geant4 code. The number of leakage neutrons from the sections of the uranium target surrounded by the lead shielding and the number of leakage neutrons from lead were determined. The total number of fissions in the setup QUINTA was determined. Experimental values of reaction rates for the produced nuclei in the 127 I sample were obtained and several values of reaction rates were compared with the results of simulations. Experimentally determined fluence of neutrons in energy interval 10–175 MeV using the (n, xn) reactions in the 127 I(NaI) sample was compared with the results of simulations. Possibility of transmutation of the long-lived radionuclide 129 I in the QUINTA setup was estimated. Highlights: Natural uranium assembly was irradiated with 660 MeV protons. Fluence of fast neutrons was measured using 127 I(n, xn) reactions. Monte Carlo simulations provided the information about the number of total fissions in the assembly and number of leakage neutrons from the assembly and from the lead shielding.